Effect of alkaline de-esterified pectin on the complex coacervation with pea protein isolate under different mixing conditions. (30th June 2019) - Pillai, Prasanth K.S.; Stone, Andrea K.; Guo, Qian; Guo, Qingbin; Wang, Qi; Nickerson, Michael T.
Highlights: Pectin with lower DM would carry overall higher charge density. Alkaline de-esterification made pectin stiffer than unmodified. Initial interactions of de-esterified pectin and pea protein occurred at pHs > pI. Increased stiffness of the pectins enhanced its interaction with PPI. Optimal biopolymer interactions occurred between pHs 3.70 and 3.85. Abstract: High methoxy citrus pectin (UM88) was saponified to produce modified pectin [M(72, 42, and 9)], with different levels of degree of esterification (DE), to investigate the complex coacervation of pea protein isolate (PPI) with pectin [UM88 and M(72, 42, and 9)]. Regardless of the DE value of pectin, the critical pH corresponding to when insoluble complexes form shifted to higher pH as the mixing ratio increased. The maximum amount of coacervates formed at a biopolymer-mixing ratio of 8:1, 8:1, 10:1 and 15:1 for PPI with UM88, M72, M42, and M9, respectively. Maximum interactions for the protein-pectin admixtures occurred between pH 3.70 and 3.85. PPI complexed with modified pectin displayed greater interactions under their optimal mixing conditions compared to the unmodified pectin. The de-esterification of pectin resulted in more rigid and stiffer pectin, which enhanced its interaction with PPI by shifting the critical parameters to a higher value.